The Exhibition on Catholic Culture: Dialogues and Negotiations at the Vietnam Museum of Ethnology. (April 2016) - Van Huy, Nguyen; Thi Ha, Vu; Thi Thanh Tam, Vu
Abstract: The first exhibition in Vietnam to feature Vietnamese Catholics was held from December 10, 2008 to June 10, 2009 at the Vietnam Museum of Ethnology in Hanoi. The theme of this exhibition was "Catholic Culture as an Intrinsic Part of Vietnamese Culture." The exhibition was organized by a State‐run museum against a background of difficult relations between the State and its Catholic communities. This article explores how the exhibition was conceived, and how the ideas of the curators were implemented by examining negotiations among different stakeholders involved in the exhibition.